In-situ high-temperature tensile testing of a polycrystalline nickel-based superalloy. (28th June 2016) - Summers, W. D.; Alabort, E.; Kontis, P.; Hofmann, F.; Reed, R. C.
Abstract : An in-situ testing method for high-temperature time-resolved surface observations inside the scanning electron microscope is described and used to improve the mechanistic understanding of a new polycrystalline nickel-based superalloy. The in-situ observations are able to elucidate surface mechanisms of damage in different deformation regimes. Tensile tests from ambient conditions to 750 °C determine the effect of temperature on the prevalent modes of deformation. At low and intermediate temperatures, the formation of discrete slip bands and the cracking of the harder precipitates (carbides) are observed directly. Under this regime, both inter- and trans-granular failure are observed. At the highest temperatures tested, the mechanism of damage is different; the grain boundaries, their orientation and their precipitates play a crucial role. Void growth is directly observed as a consequence of small hard-particle decohesion from the matrix, within those grain boundaries of relative orientation which promotes the shear deformation. As deformation increases, voids grow and coalesce, forming grain boundary cracks thus leading to catastrophic intergranular failure: this manifests itself as low-ductility particularly at the high-temperature conditions.